Design, synthesis and evaluation of fluorescent CB2 cannabinoid receptor ligands - Holt, Christopher James (2009)
Cannabis has been used as a medicinal and natural product for thousands of years. Whether it has been used to make rope or paper, or been used to treat pain or depression, cannabis has always had a place in human civilisation.